Ética profesional en el desempeño docente - Falcón Toscano, Lesly Gabriela (2017)
The study of “Professional Ethics in Teaching Performance", it optimizes a communication among teachers at "Ana Páez” Educational Unit encouraging the Ethical Value practice, that problem affects the interrelationship of educational community (teachers and students). Thus, this research project was developed under the socio-educational form, with a qualitative-quantitative approach, explanatory, bibliographical and field documentary; with the application of inductive, deductive, analytical and dialectical methods, which helps to strengthen and apply research. Over time, education has had to face several challenges, the main challenge being to fulfill and carry out a good teaching - learning process, in order to improve the needs of society. At Educación General Básica (EGB) used to have a subject called values, but nowadays it is mandatory to introduce in each subject, education in values during the academic year….